Penurunan Kadar Glukosa Darah Pada Pasien Diabetes Mellitus Tipe 2 Melalui Sekawat Biqul (Senam Kaki Dengan Sholawat Thibbil Qulub) Di Wilayah Kerja Puskesmas Kamoning Sampang - Istibsaroh, Faridatul; Arif, Ahmad Zaini; Hasanah, Nur; Ika W, Mei Lestari; Dewi, Wiwin Hendriyani (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: To analyze the effectiveness of SEKAWAT BIQUL on blood glucose levels in Diabetes Mellitus patients. Methods: This study used a quasy-experimental design with a pre-post test control group design approach, The sample in this study was 32 respondents divided into 16 interventions group and 16 control groups. The sampling technique is consecutive sampling. Results:The results of the Mann Whitney test showed (p=0.006), which means that SEKAWAT BIQUL was effective on blood glucose levels in type 2 DM respondents in the treatment group. Conclusion: Implementation of SEKAWAT BIQUL can reduce blood glucose levels so that very effective non-pharmacological therapy for DM patients